Legal Certainty and Reformulation of Regulations on The Granting of Industrial Plantation Forest Management Permits - Matthew Febrian Otniel Lambok Hutasoit; Muhammad Helmi Fahrozi (Law Development Journal, 2025)
This study aims to examine the legal certainty of civil relations between indigenous peoples who hold land rights and holders of Industrial Forest Plantation (HTI) permits in the context of the disharmony between the Basic Agrarian Law and the Forestry Law. The research focuses on the case of the Minister of Forestry Decree No. 346/Menhut-II/2004, which granted a permit to PT Wirakarya Sakti covering an area of ±293,812 hectares in Jambi Province, overlapping with the customary lands of 134 villages and triggering prolonged agrarian conflicts. A normative juridical method was used with a case, legislation, and conceptual approach to analyze the conflict of norms and overlapping authorities. This study identified three main forms of legal uncertainty: the unclear status of land in forest areas, unfair access to resources, and the absence of effective dispute resolution mechanisms. This disharmony is exacerbated by overlapping authorities between the Ministry of Environment and Forestry and the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, as well as weak verification of land status prior to the issuance of permits. Reformulation of HTI licensing regulations is recommended through institutional harmonization of authority, substantive revision of the Forestry Law, integration of the principles of Free, Prior, and Informed Consent, strengthening of transparency and public participation, and strengthening of evaluation and sanction mechanisms to create fair and sustainable HTI governance.